2021
DOI: 10.31219/osf.io/6mrhc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Houston, we Have a Pandemic: Technical Difficulties, Distractions and Online Student Engagement

Abstract: The COVID-19 pandemic has brought sudden changes to various facets of daily life, including a massive shift to remote education. College students rely on technology to attend class and interact with instructors and peers, while possibly facing technical and situational difficulties at home. Considering the unprecedented situation, the purpose of the present study was to extend online student engagement literature during the COVID-19 pandemic. The survey sample consisted of 78 undergraduate students, recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Low levels of technical difficulties perception, respectively, of diversity of techniques are associated with high levels of online learning engagement, while high levels of online self-efficacy are associated negatively with technical difficulties perception, respectively, with diversity of techniques, which confirms the fact that there is variability in the modality of students' answers. The more recent literature on this topic (Kostaki and Karayianni, 2021) points out that self-efficacy moderates the relation between technical difficulties and learning engagement, therefore students who were not confident in their computer skills and encountered technical difficulties had lower engagement scores than those with higher online self-efficacy facing a similar situation, which opens new directions in research.…”
Section: Sources Of Stress and Learning Engagementmentioning
confidence: 99%
“…Low levels of technical difficulties perception, respectively, of diversity of techniques are associated with high levels of online learning engagement, while high levels of online self-efficacy are associated negatively with technical difficulties perception, respectively, with diversity of techniques, which confirms the fact that there is variability in the modality of students' answers. The more recent literature on this topic (Kostaki and Karayianni, 2021) points out that self-efficacy moderates the relation between technical difficulties and learning engagement, therefore students who were not confident in their computer skills and encountered technical difficulties had lower engagement scores than those with higher online self-efficacy facing a similar situation, which opens new directions in research.…”
Section: Sources Of Stress and Learning Engagementmentioning
confidence: 99%
“…Some early studies exploring online learning as part of the response to the global pandemic have been published, showing a mixed picture. Kostaki and Karayianni ( 2021 ) explored student engagement in online courses during the pandemic to find an unsurprising negative correlation with technical difficulties. Garris and Fleck ( 2020 ) surveyed students across the US to ask them to provide an evaluation of one of their online courses.…”
Section: Introductionmentioning
confidence: 99%
“…Additional factors potentially contributing to the overall dissatisfaction with the course include the lack of clinical experiences in the redesigned ophthalmology curriculum, reduced digital efficacy and technical issues. Kostaki et al found that student engagement negatively correlated with technical difficulties and home distractions [ 47 ]. Furthermore, they reported that computer self-efficacy positively contributed towards engagement as students could remedy technical difficulties [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kostaki et al found that student engagement negatively correlated with technical difficulties and home distractions [ 47 ]. Furthermore, they reported that computer self-efficacy positively contributed towards engagement as students could remedy technical difficulties [ 47 ]. Brockman et al compared student perceptions of an online or in-person microbiology laboratory and found that while students have positive perceptions of digital online activities there was still a significant preference for a blend of online and in-person practical activities [ 48 ].…”
Section: Discussionmentioning
confidence: 99%